Integrated effects of anaerobic soil disinfestation and beneficial microbes in strawberry production - Baker D. Aljawasim; Patricia Richardson; Chuansheng Mei; Robert L. Chretien; J. Scott Lowman; Jayesh B. Samtani (PLoS ONE, 2025)
Fruit rot diseases, including anthracnose fruit rot and Botrytis fruit rot caused by Colletotrichum acutatum and Botrytis cinerea , respectively, pose major challenges to sustainable strawberry production in the United States. Organic and small-scale growers require non-chemical alternatives to soil fumigation due to health, regulatory, or technical constraints. This study evaluated anaerobic soil disinfestation (ASD), beneficial bacteria ( Bacillus velezensis IALR619 and TerraGrow-a commercial product), and their combinations as integrated strategies to manage fruit rot, suppress weeds, and enhance fruit quality. A split-plot field trial was conducted over two growing seasons (2022/23–2023/24) at the Hampton Roads AREC in Virginia Beach, VA. ASD significantly reduced AFR, BFR, and overall fruit rot incidence compared to non-fumigated and Pic-Clor 60-fumigated controls. Post-plant inoculation with B. velezensis IALR619, TerraGrow, or TerraGrow + Oxidate 5.0 further decreased AFR incidence. ASD also reduced weed density and improved postharvest fruit firmness, total soluble solids, and juice pH. B. velezensis IALR619 inoculation enhanced fruit firmness compared to uninoculated controls. The beneficial microbes with ASD offer a promising alternative to synthetic fumigation, reducing fungicide usage by organic growers, small farms, and resource-limited growers, while also improving strawberry fruit quality.